Comparison Analysis Of Financial Performance Before And After The Merger (Case Study at PT. Bank Danamon Indonesia Tbk and PT. Bank Syariah Indonesia Tbk) - Dede Hertina; Laila Zafira Arizona (Enrichment : Journal of Management, 2022)
This study aims to analyze the financial performance before and after the merger at PT. Bank Danamon Indonesia Tbk which merged in 2019 and PT. Bank Syariah Indonesia Tbk which will merge in 2021. This study uses a quantitative approach by using secondary data obtained from the official website of each bank. The valuation variables used in this study consist of the current ratio, return on assets, return on equity, debt to equity ratio, and total asset turnover. The analytical method used to answer the hypothesis is to use the normality test and paired sample T-test. The results of hypothesis testing indicate that there is no significant difference to all financial ratios at PT. Bank Danamon Indonesia Tbk and PT. Bank Syariah Indonesia Tbk.